Pengembangan E-Modul Kimia Materi Larutan Penyangga Berbasis Kontekstual pada Pembelajaran Daring Siswa SMA KELAS XI - Aminah, Aminah; Muntari, Muntari; Wildan, Wildan; Loka, I Nyoman (FKIP University of Mataram, 2024)
This research includes development research (R&D) which aims to produce the development of contextual-based chemical e-modules on buffer solution materials and to determine the quality of the developed e-modules in terms of the level of validity and practicality. A contextual-based chemistry e-module on buffer solution material has been successfully developed. This study used 4-D development model that has reached the develop stage. The subjects in this study were 2 experts for the validity test, 2 chemistry teachers and 60 students of SMAN 1 Sakra for the e-module practicality test. The data taken in this study were obtained from observations, questionnaires, and documentation. The e-module that has been developed is declared very valid by the validator in terms of several aspects of the assessment with an average value of 83.25% and very practical with an average percentage of chemistry teachers and students respectively 91.13% and 87.82%. The results obtained from the study indicate that the contextual-based chemistry e-module on the buffer solution material that has been developed meets the very valid criteria and is very practical for use in the online learning process and face-to-face learning.